2016
DOI: 10.1080/07315724.2016.1150223
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Supplementation withp-Synephrine Alone and in Combination with Caffeine on Metabolic, Lipolytic, and Cardiovascular Responses during Resistance Exercise

Abstract: Supplementation with S and SCF increases lipolysis primarily at rest and increases VO, EE, and fat oxidation rates 30 minutes following RE. No HR changes were observed unless caffeine was added.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 47 publications
1
44
1
Order By: Relevance
“…For example, Ratamass and colleagues [31] reported that ingestion of 100 mg of p -synephrine increased lipolysis primarily at rest as well as post-exercise oxygen uptake, energy expenditure, and fat oxidation. Sale et al [33] reported that ingesting a supplement containing 6 mg of p- synephrine, 150 mg caffeine, and 150 mg catechin polyphenols increased resting and exercise carbohydrate oxidation rates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ratamass and colleagues [31] reported that ingestion of 100 mg of p -synephrine increased lipolysis primarily at rest as well as post-exercise oxygen uptake, energy expenditure, and fat oxidation. Sale et al [33] reported that ingesting a supplement containing 6 mg of p- synephrine, 150 mg caffeine, and 150 mg catechin polyphenols increased resting and exercise carbohydrate oxidation rates.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if p-synephrine is expected to mobilize fatty acids from other tissues (e.g., adipose tissue), no coordinated stimulation of their oxidation can be expected in the liver except that one given by its increased availability. Modest increases in the levels of circulating nonesterified fatty acids by p-synephrine have indeed been suggested to occur in humans based on the finding that administration of the drug resulted in higher glycerol levels [27]. It should be noted, however, that with reference to the ingestion of C. aurantium extracts, an extra stimulation of the oxidation of exogenous fatty acids in the liver could be expected, in theory at least, by virtue of their contents in p-octopamine [11].…”
Section: Resultsmentioning
confidence: 99%
“…9 p-Synephrine augments lipolysis, energy expenditure, and fat oxidation at rest and during the latter stages of recovery (ie, 30 minutes) following acute resistance exercise. 4,10 It has also been shown to increase energy and appetite control. 14,15 Caffeine has been shown to increase alertness and wakefulness, feelings of well-being, concentration and focus, and mood.…”
Section: P-synephrinementioning
confidence: 99%
“…Various effects on lipid metabolism, 10,24,25,57 metabolic rate, 52,58 sport performance, 4 and energy production 11 have been demonstrated at these doses, as well as higher doses of p-synephrine that do not produce cardiovascular effects. 4,10,11,24,25,52,57,58 Therefore, adequate blood levels are achieved to produce these effects without cardiovascular effects. The question remains whether cardiovascular effects can be attained at doses of p-synephrine >100 mg. To date, doses of up to 100 mg p-synephrine per day for 60 days have been shown to be without adverse effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation